ANALISIS PENERAPAN AKUNTANSI SYARIAH BERDASARKAN PSAK 407 PADA PEMBIAYAAN IJARAH MULTIJASA DI BMT BINA INSAN SEJAHTERA KOTA JAMBI - Nisa Rara Aulia; Khairiyani, Khairiyani; Kurniyati, Kurniyati (Nusantara Hasana Journal, 2026)
Multi-service ijarah financing is one of the financing products at BMT that requires accounting records referring to PSAK 407. However, the implementation of this standard has not been fully optimal due to limited understanding of managers. This study aims to determine the accounting recording practices of multi-service ijarah financing at BMT Bina Insan Sejahtera, Jambi City, assess its compliance with PSAK 407, and determine the reasons for the suboptimal implementation. This study uses a qualitative approach with case study methods and field research. Data were collected through interviews, documentation, and observation, then analyzed through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the recording of multi-service ijarah financing has been carried out in an orderly manner, with the recognition of ijarah receivables and the separation of principal, service income (fees), and alms. However, this practice is not fully compliant with PSAK 407, particularly in the presentation and disclosure aspects of financial statements. This discrepancy is influenced by limited understanding, lack of training, and the non-physical nature of the contract. This study concludes that the implementation of multi-service ijarah accounting at the BMT is quite good, however, improvements are still needed to align with PSAK 407 through training and mentoring from relevant agencies.